Giant gauge factor of Van der Waals material based strain sensors - Wenjie Yan (Nature Portfolio, 2021)
The Gauge factor (GF) enhancement in strain sensors remains a key challenge. Here the authors leverage the piezoelectric and photoelectric effects in a class of van der Waals materials to tune the GF, and obtain a record GF up to 3933 for a SnS2-based strain sensor.